MedTracker: A BLE-Based Indoor Localization System for Tracking Portable Medical Devices in Hospital Environments - Oliveira, Higor D.; Sarmento, Elisa M.; Saleme, Eduardo S.; Souza Jr, Luis A.; Vivas, Gustavo C.; Trindade, Daniel R.; Villaça, Rodolfo S.; Pacheco, André G. C. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
The misplacement and inefficient tracking of Portable Medical Devices (PMDs) represent a persistent operational challenge in hospital environments, leading to delays in care delivery and increased burden on medical staff. This paper presents MedTracker, an indoor localization tool based on Bluetooth Low Energy (BLE), designed for real-time asset tracking in healthcare facilities. The system employs BLE tags attached to monitored devices and strategically deployed ESP32-based gateways that forward signal data to a central server. By combining BLE signals and filtering techniques with machine learning classification and clustering algorithms, MedTracker is capable of inferring room- and floor-level device location, as well as detecting location changes over time. The proposed tool was motivated by practical demands observed at a public university hospital and validated through experimental evaluation, demonstrating its effectiveness as a scalable and deployable solution for hospital asset management.